2009
DOI: 10.1080/08998280.2009.11928456
|View full text |Cite
|
Sign up to set email alerts
|

Appropriateness of Sling Immobilization to Prevent Lead Displacement After Pacemaker/Implantable Cardioverter-Defibrillator Implantation

Abstract: After pacemaker/implantable cardioverter-defibrillator (pacemaker/ICD) implantation, patients are often required to immobilize the affected arm with a sling to minimize the risk of lead displacement. We examined whether performing a resistive range-of-motion exercise protocol after pacemaker/ICD surgery would result in lead displacement and, therefore, whether sling immobilization and activity restrictions are justified. Ten subjects who had undergone pacemaker/ICD surgery performed four individual resistive r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…In their pilot study, Naffe et al (2009) asked their study subjects to perform exercises that involved lifting 1-or 2 pound weights and raising their arm on the accessed side above shoulder level and above the head in a "military press", "diagonal raise", "overhead triceps extension" and "frontal raise". No lead displacement occurred, suggesting that there was no evidence for immobilising the arm postoperatively [10].…”
Section: Studies On Lead Displacements and Mobilisationmentioning
confidence: 99%
See 1 more Smart Citation
“…In their pilot study, Naffe et al (2009) asked their study subjects to perform exercises that involved lifting 1-or 2 pound weights and raising their arm on the accessed side above shoulder level and above the head in a "military press", "diagonal raise", "overhead triceps extension" and "frontal raise". No lead displacement occurred, suggesting that there was no evidence for immobilising the arm postoperatively [10].…”
Section: Studies On Lead Displacements and Mobilisationmentioning
confidence: 99%
“…Common practice remains to encourage limited arm movement after cardiac device implantation, as this is thought to prevent lead displacement. Typical advice ranges from "Don't use your arm for 24 hours", "Don't lift more than 10 pounds for 2 weeks" to "Don't lift your arm over your shoulder for 6 weeks" [13]. Patients may get disparate advice from different members of the clinical team, which can lead to further confusion.…”
Section: Introductionmentioning
confidence: 99%
“…Appropriate postoperative patient education on arm movement is important, as prolonged restricted arm movement may lead to adhesive capsulitis (frozen shoulder) leading to prolonged postoperative pain. 30 Multiple statements on recommendations for opioid use in managing acute postoperative pain have been published. 22,31 The Dr. Robert Bree collaborative categorized procedures into various types, based on expected duration of recovery.…”
Section: Discussionmentioning
confidence: 99%
“…11 However, after the first year following implantation, limitations become permanent and are not self-resolved. 12,13 Although studies have shown that early mobilization after CIED implantation is safe, [14][15][16][17] some physicians habitually prefer to temporarily immobilize the arm with a sling or restrict arm movements above the shoulder level. 18,19 Also, patients may extend this period of their own accord to avoid the risk of device malfunction.…”
Section: Introductionmentioning
confidence: 99%